Analysis of the Effect of Learning Interest, Learning Motivation and Self-Awareness on Arabic Learning at Madrasah Aliyah Bilingual Batu - Desy Kumalasari; Sri Hardianti Rukmana; Abdullah Majid; Ryan Nurdiana; Syuhadak (South Sulawesi Education Development (SSED), 2024)
This study aims to test the independent variables consisting of learning interest, learning motivation, and self-awareness of the dependent variable, namely Arabic language learning. The research approach used is quantitative with the PLS 3 SEM method. The data collection method uses questionnaire distribution techniques and sample selection in this study uses a sample quota, namely the number of respondents taken has been determined by the sample size. In this study, the sample used as many as 85 respondents showed the results of: (H1) Accepted, that is, there is a significant influence of student interest in learning Arabic with path coeficient (0.962) and p-value (0.000 < 0.05). (H2) Rejected that is, there is no significant influence of student motivation on Arabic learning with path coeficient (0.011) and p-value (0.699 > 0.05). 3. (H3) Rejected i.e. there is no significant influence of students' self-awareness on Arabic language learning with path coeficient (0.020) and p-value (0.496 > 0.05). while the R-square value is the result of measuring Arabic learning variables (0.949). This value means that the Arabic learning variable is influenced by the independent variable by 94.9%, while the rest is influenced by other factors. While each of the rest is influenced by other factors outside the variables studied. researchers provide recommendations to teachers or schools to carry out special assistance, both subject teachers and counseling guidance in order to strengthen aspects of motivation and self-awareness. Keywords: Learning Interest, Learning Motivation, Self Awareness, Arabic Learning